Cidade, consumo e práticas espaciais em Ituiutaba – MG: segmentação e fragmentação socioespacial - Souza, Jéssica Silva (2018)
The complexity that characterizes urban space nowadays shows the need to understand how consumption and practices associated with it interact in the production of cities at the current stage of the urbanization process. This is because we live in a period marked by the centrality of consumption, as opposed to other times when much of the dynamics and processes were directed on production activities. In this context, this dissertation aims to understand the relationships between commerce, consumption and the city based on the space practices of the city dwellers in Ituiutaba-MG, in order to deal with the socio-spatial fragmentation process. The choice of this city is due to the fact that the changes occurred in the context of the urban structuring and the structuring of the city, based on the transformations verified over the last years in Ituiutaba, as well as the need to understand processes related to the segmentation of consumption and fragmentation in non-metropolitan realities. From a theoretical review on the different themes that support this study, a qualitative perspective of research was adopted, having as main methodological procedure the interviews with the city dwellers of different social segments. The results pointed to certain tendencies towards the segmentation of consumption, although it does not constitute a process of social and spatial fragmentation. This is because, in Ituiutaba, the spatial practices of city dwellers of different social segments occur practically in the same spaces, which makes possible the encounter, the coexistence and the sociability with regard to consumption.